Primo Levi épistémologue des camps - Enrico Mattioda (Laboratoire Italien)
After publishing If This Is a Man in 1947, Primo Levi wished to be recognised not only as a survivor but also as a writer. In this book, he represented the extermination camp in a different way from the sociological perspective given by other survivors. As a scientist, his mindset did not consider hierarchy and the pyramidal pattern normally used to describe the totalitarian regime; instead, he used a pattern based on the idea of the feedback loop and on the return to homeostasis. His essential question was to comprehend the core of the dynamics of the Lager: in the following years, he knew that the determinist approach was not the best tool for the purpose of explaining complex systems like history or the birth of racism. He thus took an interest in chaos theory, which was more useful to describe complex systems and long-lasting phenomena. He most likely gained fundamental insight from the application of Rene Thom’s catastrophe theory to the description of ambiguous images and sudden shifts in behaviour. For Levi, the concept of ambiguity was a basic fundamental for the comprehension of the Nazi camps, and from there he began to develop a theory of intermediate states, i.e. states of transition or corruption from one condition to another one. This theoretical premise enabled him to elaborate on the concept of the “grey zone”: the zone that both separates and connects masters and servants, persecutors and victims.